Trauma, attachment, and family permanence : fear can stop you loving - Archer, Caroline, 1948-; Burnell, Alan. (London ; New York : Jessica Kingsley Publishers, 2003)
Exploring the complex issues of trauma, attachment and family placement, the contributors to this book provide a variety of complementary perspectives on practice in this area. Focussing on how to integrate attachment theory and developmental psychology in practice with adopted or fostered children, they emphasise the need for understanding of early trauma and its effect on child development. Examining multiple aspects of work with children who are unable to live with their birth families, the book includes contributions on: new approaches to matching children with families; effective manageme.
Adoption and permanence today: a discussion / Adrian Briggs -- The 'coherent narrative': realism, resources and responsibility in family permanence / Elsie Price -- Setting up the loom: attachment theory revisited / Alan Burnell with Caroline Archer -- Weft and warp: developmental impact of trauma and implications for healing / Caroline Archer -- Clinical concepts and caregiving contexts: a consultant's perspective / Jeanne Magagna -- 'A hard day's night': a parent's perspective -- Jenny and Marty's story / Jay Vaughan -- Assessment: a multidisciplinary approach / Alan Burnell -- Rationale for the intensive programme ; The drama of adoption ; The drama unfolds / Jay Vaughan -- Contact as therapy / Alan Burnell -- Holding the fort ; Hands on help / Christine Gordon -- Dificulty with learning or learning to be difficult? / Griselda Kellie-Smith -- Weaving together the threads: families with futures / Caroline Archer.
Includes bibliographical references (pages 309-324) and indexes.
Print version record.
Added to collection customer.56279.3
Keywords: Psychic trauma in children; Attachment behavior in children; Families -- Psychological aspects; Attachment behavior; Parent and child; Post-traumatic stress disorder; Children; Object Attachment; Parent-Child Relations; Stress Disorders, Post-Traumatic; Adoption -- psychology; Child; Foster Home Care -- psychology; Traumatisme psychique chez l'enfant.; Attachement chez l'enfant.; Familles -- Aspect psychologique; Attachement; Parents et enfants; État de stress post-traumatique.; Enfants; children (people by age group); Sociology: Family & Relationships; MEDICAL -- Pediatrics; HEALTH & FITNESS -- Children's Health; Post-traumatic stress disorder; Parent and child; Children; Attachment behavior; Attachment behavior in children; Families -- Psychological aspects; Psychic trauma in children